Probing the deployment of peripheral visual attention during obstacle-crossing planning - Malik, Raza N.; Marigold, Daniel S.; Chow, Mason; Lam, Tania (Frontiers in Human Neuroscience, 2022)
Gaze is directed to one location at a time, making peripheral visual input important for planning how to negotiate different terrain during walking. Whether and how the brain attends to this input is unclear. We developed a novel paradigm to probe the deployment of sustained covert visual attention by testing orientation discrimination of a Gabor patch at stepping and non-stepping locations during obstacle-crossing planning. Compared to remaining stationary, obstacle-crossing planning decreased visual performance (percent correct) and sensitivity (d') at only the first of two stepping locations. Given the timing of the first and second steps before obstacle crossing relative to Gabor patch presentation, the results suggest the brain uses peripheral vision to plan one step at a time during obstacle-crossing, in contrast to how it uses central vision to plan two or more steps in advance. We propose that this protocol, along with multiple possible variations, presents a novel behavioural approach to identify the role of covert visual attention during obstacle-crossing planning and other goal-directed walking tasks.